London and beyond Essays in honour of Derek Keene - Davies, Matthew; Galloway, James A. (IHR Conference Series, 2012)
This volume contains selected papers from a major conference held in October 2008 to celebrate the 20th anniversary of the setting up of the Centre for Metropolitan History at the IHR, and the contribution of Professor Derek Keene to the Centre, the IHR and the wider world of scholarship.